Pengaruh Kepemimpinan, Disiplin Kerja, Etos Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di Perusahaan Umum Daerah Air Minum (PUDAM) Tirta Bina - Sahputra, Ali (Jurnal Manajemen Akuntansi (JUMSI), 2021)
This study aims to determine the Influence of Leadership, Work Discipline, Work Ethic And Work Environment on Employee Performance In the Company's Common Area Drinking Water (PUDAM) Tirta Development. This type of research is Associative Research. Data collection in this Research was conducted through a survey approach with descriptive research type is quantitative with the spread questionnaires to 70 respondents, while the population used in this research is Employees of the Company Common Area Drinking Water (PUDAM) Tirta Bina KabupatenLabuhanbatu. The technique of data collection is done by interview, questionnaire and documentation study. The data analysis tool used in this study using SPSS (Statistical Product Sofware Solution).Data analysis in this research is descriptive analysis, multiple linear regression analysis, hypothesis testing using the test of significant partial test (t test), testing significant simultaneous (test F), and test the coefficient of determination (R2). The results of this study indicate that the partial test (t test) note that the Variable Kepemimpinanberpengaruh positive and significantly to the Performance of Employees. Variable Disciplined Work affects positively and significantly on the Performance of Employees. Variable Work Ethic affects positively and significantly on the Performance of Employees. Then Work Environment Variables have a positive and significantly to the Performance of Employees In the Company Common Area Drinking Water (PUDAM) Tirta Development.On testing simultaneously (F test) note that Leadership, Work Discipline, Work Ethic and Environment Kerjaberpengaruh positive and significantly to the Performance of Employees In the Company Common Area Drinking Water (PUDAM) Tirta Development.Through testing the coefficient of determination (R Square) amounted to 0.523 mean: 52.3% and factors of Employee Performance In the Company of the Common Area Drinking Water (PUDAM) Tirta Development can be explained by the Leadership, Work Discipline, The Work ethic and the Work Environment. While the remaining 47.7% of it can be explained by other factors not examined in this study.